Romantic children, brazen girls? An exploration of the girl-child’s representation in and around Nabokov’s Lolita and three derivative novels - Visser, Sandra (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (English))--University of Stellenbosch, 2010.